2021
DOI: 10.3389/fimmu.2020.598566
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytes Are the Control Tower That Manages Adipose Tissue Immunity by Regulating Lipid Metabolism

Abstract: Accumulating evidence reveals that adipose tissue is an immunologically active organ that exerts multiple impacts on the regulation of systemic energy metabolism. Adipose tissue immunity is modulated by the interactions between adipocytes and various immune cells. Nevertheless, the underlying mechanisms that control inter-cellular interactions between adipocytes and immune cells in adipose tissue have not been thoroughly elucidated. Recently, it has been demonstrated that adipocytes utilize lipid metabolites a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 110 publications
0
8
0
Order By: Relevance
“…These DEGs included more than 20 genes related to antigen processing and presentation, innate immunity and chemokines, which connected immune and inflammatory response with lipid metabolism during adipocyte hypertrophy [ 23 ], and were indispensable for the cross-talk between adipocytes and immune cells in adipose tissues [ 63 ]. Apparently, HG-induced adipocytes exhibited a pronounced “immune-like” capability that could activate and recruit immune cells to dialogue with themselves [ 64 ]. This could be related to the positive role of the immune-inflammatory response in maintaining the adipose tissue microenvironment to promote healthy adipocyte expansion [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…These DEGs included more than 20 genes related to antigen processing and presentation, innate immunity and chemokines, which connected immune and inflammatory response with lipid metabolism during adipocyte hypertrophy [ 23 ], and were indispensable for the cross-talk between adipocytes and immune cells in adipose tissues [ 63 ]. Apparently, HG-induced adipocytes exhibited a pronounced “immune-like” capability that could activate and recruit immune cells to dialogue with themselves [ 64 ]. This could be related to the positive role of the immune-inflammatory response in maintaining the adipose tissue microenvironment to promote healthy adipocyte expansion [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that licoricidin administration to mice by both oral gavage and fat pad injection effectively stimulated beige fat thermogenesis but had little effect on BAT thermogenesis. A possible explanation for this result is that adipose tissue is heterogeneous, and its function is dynamically orchestrated by the microenvironment within the tissue such as T cells and macrophages 43 , 44 . Alternatively, given that both β3-AR and UCP1 are highly enriched in BAT 45 , 46 , low doses of licoricidin may be insufficient to further increase BAT thermogenesis, demonstrating a beige fat-specific function of licoricidin in thermogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Pref‐1 inhibits the adipogenic differentiation of adipocytes by inhibiting the early adipogenic differentiation factors C/EBPβ and C/EBPδ (da Silva & Durandt, 2020; Park & Kim, 2020; Unger, 2003). Park et al (2020) proved that with the increase of adipogenic differentiation time, the expression level of CAVIN3 gradually increased, and the expression of Pref‐1 gradually decreased in 3T3‐L1 cells. Further studies have found that CAVIN3 promotes adipogenic differentiation by down‐regulating the tumor necrosis factor α converting enzyme (TACE) and inhibiting the function of Pref‐1 (Park & Kim, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue is an important energy storage organ, which is widely involved in the biological metabolic processes of the body. Fat deposition affects the physiological functions and economic traits of animals (Park et al, 2020). Aberrant fat deposition may lead to poor disease resistance, decrease the production performance of pigs, and reduce feeding efficiency.…”
Section: Introductionmentioning
confidence: 99%